Termiticidal, biochemical, and morpho-histological effects of botanical based nanoemulsion against a subterranean termite, Odontotermes Formosanus Shiraki - Nasser, Raghda; Ibrahim, Ezzeldin; Fouad, Hatem; Ahmad, Farhan; Li, Wuhan; Zhou, Qihuan; Yu, Ting; Chidwala, Nooney; Mo, Jianchu (Frontiers in Plant Science, 2024)
Recently, the use of nanopesticides has shown significant efficacy in the control of many pests. However, the effect of nanopesticides, especially nanoemulsions, on suppressing termites, Odontotermes formosanus (Shiraki, 1909) (O. formosanus), has not been studied yet. Therefore, this study aimed to produce nanoemulsions of the essential oils of eucalyptus (Eucalyptus globulus Labill; E-EO) and nutmeg (Myristica fragrans Houtt; N-EO) to suppress O. formosanus. The analysis of eucalyptus nanoemulsion (E-NE) and nutmeg nanoemulsion (N-NE) was confirmed by using UV-Vis, dynamic light scattering, zeta potential, transmission electron microscopy, scanning electron microscopy, and energy dispersive spectroscopy. In addition, chemical analysis by Gas Chromatography with a mass spectrometer (GC-MS) exhibited the major constituents of E-NE and N-NE. The principal chemical components of E-NE included D-limonene, eucalyptol, 1,5-cyclooctadiene,3,4-dimethyl, benzene, and 1-methyl-3-(1 methylethyl)-, while the main constituents in N-NE were cyclohexane,1-methylene-4-(1 methylethenyl)-, eucalyptol, and L-. alpha. -terpineol. The mortality rates were 100% and 99.53%, respectively, after 24 hours of treatment with a concentration of 140 mg/mL, compared to 23.43% and 43.55%, respectively, from E-EO and N-EO treatment. These results refer to the essential oils’ nanoemulsion as far more effective than the essential oils themselves. Furthermore, the effects of E-NE and N-NE on detoxification enzymes such as acetylcholinesterase, carboxylesterase, acid and alkaline phosphatase were investigated, as well as total protein concentrations, and the results have been found to be significantly increasing or decreasing in comparison with control. Besides, histological and morphological alterations found post exposure to E-NE and N-NE were shown. Overall, the results from this study clearly indicate that the nanopesticide-formulated nanoemulsions may have great potential to be used as novel, environmentally safe insecticides for controlling O. formosanus.